2003
DOI: 10.1007/bf03256653
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Interleukin-5 Monoclonal Antibodies

Abstract: Descriptive studies have shown an association between eosinophils, interleukin (IL)-5 and pathophysiological processes in patients with atopic asthma. These observations have led to an interest in the eosinophil as the pathogenic cell responsible for many of the clinical features of asthma including symptoms of wheeze, shortness of breath and cough, along with the physiological events such as airway hyperresponsiveness (AHR) and changes in lung function. IL-5 is one of the key cytokines responsible for eosinop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(17 citation statements)
references
References 84 publications
1
16
0
Order By: Relevance
“…That is, although the partial loss of eosinophils failed to prevent OVA-induced inflammatory responses in IL-5 −/− , these responses were abolished in IL-5 −/− /eotaxin-1 −/− mice that had a complete ablation of pulmonary eosinophils (36). The demonstrated inability to completely eliminate lung tissue eosinophils among human subjects receiving anti–IL-5 therapeutics may also represent a confounding issue that has complicated conclusions from clinical studies of asthma patients (6, 37, 38). These observations suggest that together with potential activities on T cell proliferation/activation and destructive effector activities mediated by granule protein release, the additional capability of eosinophils to mediate effector T cell accumulation in the lung may provide yet another mechanism by which eosinophils initiate and maintain the immune/inflammatory responses associated with allergic asthma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, although the partial loss of eosinophils failed to prevent OVA-induced inflammatory responses in IL-5 −/− , these responses were abolished in IL-5 −/− /eotaxin-1 −/− mice that had a complete ablation of pulmonary eosinophils (36). The demonstrated inability to completely eliminate lung tissue eosinophils among human subjects receiving anti–IL-5 therapeutics may also represent a confounding issue that has complicated conclusions from clinical studies of asthma patients (6, 37, 38). These observations suggest that together with potential activities on T cell proliferation/activation and destructive effector activities mediated by granule protein release, the additional capability of eosinophils to mediate effector T cell accumulation in the lung may provide yet another mechanism by which eosinophils initiate and maintain the immune/inflammatory responses associated with allergic asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of T lymphocytes in mouse models of allergic respiratory inflammation is also highlighted in studies showing that depletion of T cells in allergen-provoked mice inhibits asthma pathologies, including eosinophil recruitment to the lungs (2). Interestingly, although eosinophil recruitment to the lung has been a defining characteristic of allergic respiratory inflammation, occurring, for example, even in mild forms of asthma (3), causative links between pathologies and specific eosinophil-mediated activities have remained unresolved (e.g., reference 4 vs. reference 5), with some clinical studies even discounting significant roles for eosinophils (6). Instead, most papers have implied a nearly unidirectional immune regulatory mechanism by which T cells promote the inflammation of asthma with the role of eosinophils remaining ambiguous and the subject of debate.…”
mentioning
confidence: 99%
“…A capacity to reduce the influx of effector/memory CD4 + T cells into the pulmonary microenvironment is of particular importance in the context of immune-mediated lung inflammation since this population regulates many parameters of immune lung pathology (27). Indeed, several different studies have shown that inhibition of the cytokines IL-5 and IL-13 alone can lead to reduction in airway hyperreactivity, mucus hypersecretion, IgE generation, as well as eosinophil influx (2831). …”
Section: Discussionmentioning
confidence: 99%
“…47). Given the disappointing results with agents directed at eliminating eosinophils via anti-IL-5 cytokine modulation (48,49), attention may turn toward transcriptional control as a more direct means of eliciting temporary eosinophil lineage ablation. No one has successfully identified a single transcription factor or transcriptional event that uniquely defines the eosinophil lineage, although GATA factors are likely to play a pivotal role.…”
Section: -36)mentioning
confidence: 99%